Pengaruh Penerapan Safety Management System Terhadap Kualitas Pelayanan Pemanduan Lalu Lintas Udara di Perum LPPNPI Kantor Cabang Gorontalo - Janet Apta Adristy; Rany Adiliawijaya Putriekapuja; Ika Endrawijaya (Politeknik Penerbangan Indonesia Curug, 2020)
The objective of the research is to analyze how much the influence between Implementation of Safety Management System (SMS) towards Service Quality. The research conducted at Perum LPPNPI Gorontalo and Politeknik Penerbangan Indonesia Curug. Type of research is quantitative research by means of surveys with a sample of 20 respondents and an error level of 5% to ATC personnel at Perum LPPNPI Gorontalo. The data collection technique used is the Pearson Product Moment correlation followed by regression and t test. This study concludes that there is a positive relationship between the Implementation of the Safety Management System towards Service Quality with a coefficient 0.723 and a coefficient of determination 52.3%, which means that the effect of the Application of the Safety Management System on Service Quality is 52.3% and the rest is determined by other factors outside of this research. With these results, it’s hoped that it can be a source of improving and evaluating the relationship between the Implementation of the Safety Management System towards Service Quality at Perum LPPNPI Gorontalo.